2013
DOI: 10.1352/1944-7558-118.1.32
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes of Pakistani Community Members and Staff Toward People with Intellectual Disability

Abstract: The acceptance and inclusion of persons with intellectual disability can vary across cultures, and understanding attitudes can provide insight into such variation. To our knowledge, no previous study has explored attitudes toward people with intellectual disability among Pakistani community members and disability service providers. We administered the Community Living Attitudes Scale (Henry et al., 1996), a measure of attitudes toward people with intellectual disability developed in the United States, to 262 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
54
3
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(64 citation statements)
references
References 34 publications
3
54
3
4
Order By: Relevance
“…of the Libyan sample are similar to a community sample of Sunni Muslims living in Pakistan (Patka, Keys, Henry, & McDonald, 2013).…”
Section: Attitudes Towards People With Intellectual Disabilitymentioning
confidence: 58%
See 1 more Smart Citation
“…of the Libyan sample are similar to a community sample of Sunni Muslims living in Pakistan (Patka, Keys, Henry, & McDonald, 2013).…”
Section: Attitudes Towards People With Intellectual Disabilitymentioning
confidence: 58%
“…The only study we have found comparing professionals in disability support with other groups was the study mentioned earlier by Patka, Keys, Henry and McDonald (2013) of attitudes in Pakistan. Interestingly, the study found less favourable attitudes on all four sub-scales for the disability workers than the general population.…”
Section: Hypothesesmentioning
confidence: 99%
“…Although some studies had previously reported that professionals in the field of ID displayed more positive attitudes overall in comparison with other groups (Patka et al . ; Yazbeck et al . ), others identified significant group differences only on specific subscales (Henry et al .…”
Section: Discussionmentioning
confidence: 99%
“…In general, when examined in relation to findings from other studies, undergraduate students in Greece exhibit comparable scores in the Empowerment subscale, lower scores on the Exclusion subscale (meaning that they have more inclusive attitudes), higher score on the Sheltering subscale (an indication of more negative attitudes) and comparable scores in the Similarity subscale. When differences in the scores do exist, studies conducted in the Netherlands, the UK, Canada and the USA usually report more positive attitudes (Benomir et al., ; Henry et al., ; Horner‐Johnson et al., ; Ouellette‐Kuntz et al., ; Sheridan & Scior, ; Ten Klooster et al., ), whereas studies from countries such as Libya (Benomir et al., ) and Pakistan (Patka, Keys, Henry, & McDonald, ) report more negative attitudes. Scores in Greece are also comparable to those reported for Israel (Schwartz & Armony‐Sivan, ), Japan (Horner‐Johnson et al., , ) and Hong Kong (Scior, Kan, McLoughlin, & Sheridan, ) with the exception of more positive attitudes in Greece in relation to the Exclusion and Sheltering subscales.…”
Section: Discussionmentioning
confidence: 99%
“…However, nursing students (TEI of and comparable scores in the Similarity subscale. When differences in the scores do exist, studies conducted in the Netherlands, the UK, Canada and the USA usually report more positive attitudes (Benomir et al, 2016;Henry et al, 1996;Horner-Johnson et al, 2015;Ouellette-Kuntz et al, 2012;Sheridan & Scior, 2013;Ten Klooster et al, 2009), whereas studies from countries such as Libya (Benomir et al, 2016) and Pakistan (Patka, Keys, Henry, & McDonald, 2013) report more negative attitudes. Scores in Greece are also comparable to those reported for Israel (Schwartz & Armony-Sivan, 2001), Japan (Horner-Johnson et al, 2002 and Hong Kong (Scior, Kan, McLoughlin, & Sheridan, 2010) with the exception of more positive attitudes in Greece in relation to the Exclusion and Sheltering subscales.…”
Section: Attitudes Of Undergraduate Students Towards Intellectual Dmentioning
confidence: 99%